Smoke signals : the intergenerational transmission of smoking behavior - Christian Bantle; John P. Haisken-DeNew (Deutsches Institut für Wirtschaftsforschung (DIW), 2002)
In this paper, we investigate the intergenerational transmission of smoking behavior from parents to their children using data from the German Socio-Economic Panel, surveyed in 1999 including 813 youths aged 16 through 19. We find strong evidence, that parental smoking significantly increases the probability that their children likewise become smokers. Youths living in families with both parents smoking are 3.3 times more likely to smoke themselves, while a smoking father raises the probability by the factor 2.8 and a smoking mother by the factor 2.1. Further, we treat single-parent households separately and control for other socio-economic factors concerning the youths' smoking decision like household income, educational status and working status. Youths' leisure activities and personal attitudes are taken into consideration to test for determinants influencing youth smoking outside from the family context. Thus policies targeted at reducing juvenile smoking may fail, if parents' behavior is not taken into account.
Keywords: J12; I12; J13; 330; Intergenerational Transmission; Smoking; Family Composition; GSOEP; Rauchen; Generationenbeziehungen; Familiensoziologie; Deutschland